Coumarins: old compounds with novel promising therapeutic perspectives - Riveiro, Maria Eugenia (2010)
Natural as well as synthetic coumarins have recently drawn much attention due to its broad pharmacological activities. Many coumarins and their derivatives exert anti-coagulant, anti-tumor, anti-viral, anti-inflammatory and antioxidant effects, as well as anti-microbial and enzyme inhibition properties. The recognition of key structural features within coumarin family is crucial for the design and development of new analogues with improved activity and for the characterization of their mechanism of action and potential side effects. The different substituents in the coumarin nucleus strongly influence the biological activity of the resulting derivatives. Although some coumarins have been already characterized to evoke a particular biological activity, the challenge would be the design and synthesis of new derivatives with high specific activity for other pharmacological targets and define their mechanism of action to achieve new therapeutic drugs. The present review highligts the current progress in the development of coumarin scaffolds for drug discovery as novel anti-cancer agents. The major challenges about coumarins include the translation of current knowledge into new potential lead compounds and the repositioning of known compounds for the treatment of cancer.